Exercise interventions of ≥8 weeks improve body composition, physical function, metabolism, and inflammation in older adults with stage I sarcopenic obesity: a systematic review and meta-analysis - Wei, Huiting; Zhang, Jiabao; Cui, Kaiyin; Su, Hao (Frontiers in Nutrition, 2025)
IntroductionThis study aimed to assess the benefits of ≥8-week exercise interventions for stage I sarcopenic obesity (SO) without complications.MethodsRandomized controlled trials (RCTs) published from 2004 to July 2024 were searched in PubMed, Embase, Web of Science, the Cochrane Library, and EBSCO. Publication bias was assessed using funnel plots and Egger’s test. The search strategy was prospectively registered in PROSPERO (ID number: CRD42024619070). Heterogeneity (I2 > 50%) was managed using random-effects models.ResultsFifteen parallel-group RCTs involving 623 elderly adults (aged ≥60 years) were included. Exercise significantly reduced BMI (MD = −1.35, p < 0.0001), with combined exercise (CE) being the most effective (MD = −1.25, p < 0.001). Body fat percentage decreased (MD = −0.52, p < 0.00001) with CE outperforming resistance training (RT). No significant changes in fat mass or muscle mass were found (fat mass, p = 0.19; appendicular skeletal muscle mass, p = 0.88; and appendicular skeletal muscle mass index, p = 0.86). Physical function (grip strength, gait speed, and the timed Up and Go test) improved significantly (p < 0.00001); RT and CE enhanced muscle strength, with RT being superior (MD = 3.43 vs. 2.64 for CE, both p < 0.00001). Additionally, CE lowered insulin (MD = −1.73, p < 0.05) and total cholesterol (MD = −0.38, p < 0.05) levels, with marginal interleukin-6 reduction (MD = −0.51, p = 0.08). Other metabolic and inflammatory markers (glucose, triglycerides, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, tumor necrosis factor-α, and C-reactive protein) remained unchanged.Discussion≥8-week exercise improves body composition in stage I SO, with CE being the most effective for fat loss. Physical function improves with both RT and CE, and RT is better for muscle strength, while CE benefits metabolism and inflammation. We recommend that CE (≥3 times/week, 45 min/session) be used for high inflammation and RT (2–3 times/week, 60–80% of 1-RM) for low inflammation. Based on observed data trends, promoting a CE model of three aerobic exercises + two RT sessions weekly is advisable, with the intensity adjusted to 40–50% 1-RM for stage I elderly patients. Future research needs large-sample, long-term RCTs with subgroup analyses and exercise-nutrition combinations.Systematic review registrationThe search strategy was prospectively registered in PROSPERO (ID number: CRD42024619070).